(untitled) (Philadelphia, 2002)
The Manual of Physical Medicine and Rehabilitation is a unique, practical, clinical guide that focuses on the problems and management issues of patients with acute and chronic impairments. Concise form nicely complements larger, more comprehensive texts. "Washington Manual" type approach to PM&R Comprehensive, practical coverage of entire field of PM&R in easy-to-use format
Keywords: Medical rehabilitation,Medicine, physical